2006
DOI: 10.1037/1089-2699.10.1.1
|View full text |Cite
|
Sign up to set email alerts
|

The effects of individual cognitive ability and idea stimulation on idea-generation performance.

Abstract: A computer-based group idea-generation simulator was used to measure the performance of individuals with high and low cognitive ability who received high-or low-quality stimulation; high-and low-quality stimulation was operationalized by presenting controlled idea submissions from simulated group members throughout the idea-generation session. Cognitive ability and stimuli quality interacted such that the high cognitive ability/high-quality stimuli treatment achieved the highest performance. The results sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 79 publications
1
31
0
1
Order By: Relevance
“…Prior work has demonstrated a consistently positive relationship between intelligence and leadership emergence (Lord, de Vader, & Alliger, 1986;Taggar, Hackett, & Saha, 1999). We used grade point average (GPA) as a proxy for cognitive abilities (Valacich, Jung, & Looney, 2006).…”
Section: Empirical Model Specificationmentioning
confidence: 99%
“…Prior work has demonstrated a consistently positive relationship between intelligence and leadership emergence (Lord, de Vader, & Alliger, 1986;Taggar, Hackett, & Saha, 1999). We used grade point average (GPA) as a proxy for cognitive abilities (Valacich, Jung, & Looney, 2006).…”
Section: Empirical Model Specificationmentioning
confidence: 99%
“…In dispersed teams individual goal striving compensates for the lack of social pressure and aligns members' actions with the team's goals [22]. However, in a co-located context the individual's motivation is not as important a driver of individual performance compared to the pressure to conform resulting from the physical presence of other members.…”
Section: Cross-level Moderation By Team Dispersionmentioning
confidence: 99%
“…In one of the first empirical studies to examine factors predicting individual idea generation performance in a technology-supported context, Valacich et al [22] found that individual characteristics-most notably cognitive ability-play an important predictive role. They noted that the motivation of individuals was critical in translating cognitive ability into actual performance.…”
Section: Introductionmentioning
confidence: 98%
“…As individuals with greater cognitive ability tend to be more task-competent, they are more likely to emerge as leaders (Bass, 1990). As in Valacich, Jung, and Looney (2006), participants' cognitive abilities were assessed using their grade point average (GPA) as a proxy (M = 3.3 out of 4, SD = 0.6).…”
Section: Individual Covariates (Controls)mentioning
confidence: 99%